Efficacy of gabapentin for prevention of postherpetic neuralgia: study protocol for a randomized controlled clinical trial. Issue 1 (December 2017) - Rullán, Manuel; Bulilete, Oana; Leiva, Alfonso; Soler, Aina; Roca, Antonia; González-Bals, María; Lorente, Patricia; Llobera, Joan
Abstract Background Postherpetic neuralgia (PHN) is a chronic neuropathic pain that results from alterations of the peripheral nervous system in areas affected by the herpes zoster virus. The symptoms include pain, paresthesia, dysesthesia, hyperalgesia, and allodynia. Despite the availability of pharmacological treatments to control these symptoms, no treatments are available to control the underlying pathophysiology responsible for this disabling condition. Methods/design Patients with herpes zoster who are at least 50 years old and have a pain score of 4 or higher on a visual analogue scale (VAS) will be recruited. The aim is to recruit 134 patients from the practices of general physicians. Participants will be randomized to receive gabapentin to a maximum of 1800 mg/day for 5 weeks or placebo. Both arms will receive 1000-mg caplets of valacyclovir three times daily for 7 days (initiated within 72 h of the onset of symptoms) and analgesics as needed. The primary outcome measure is the percentage of patients with a VAS pain score of 0 at 12 weeks from rash onset. The secondary outcomes measures are changes in quality of life (measured by the SF-12 questionnaire), sleep disturbance (measured by the Medical Outcomes Study Sleep Scale), and percentage of patients with neuropathic pain (measured by the Douleur Neuropathique in 4 Questions). Discussion Gabapentin is an anticonvulsant type of analgesic that could prevent the onset of PHN by its antihypersensitivity action in dorsal horn neurons. Trial registration ISRCTN Registry identifier:ISRCTN79871784 . Registered on 2 May 2013.